The Logic of Sensation and Fantasy as a Step of Art Creation Through Practice-Based Research - Budiawan, Hery (Resital: Jurnal Seni Pertunjukan, 2023)
ABSTRACTThe objective of this study is to identify a stage of art creation, especially composition, where the sensations and fantasies of a composer can be understood in detail based on logic of sensation (Deleuze) and fantasy (Freud). Every work of art produced is not just a sensation or a fantasy of the artist put into the work. However, that process has its logic. Sensations and fantasies in the creation of art work are highly essential and may continue to occur until the artwork is produced. In this study the author implemented practice-based research where experience and work become the basis of a study with various approaches: literature study, content analysis, musicology, philosophy, experimental, and several things that corroborate practice-based research. The result of this study is a method of art creation with several stages that need to be done, even already done by a creator; aesthetic experience, body rhythm, chaos, fantasy, and force. These five stages are at least an interesting reference in the process of artwork and reveal that our logic of sensations and fantasies can work properly. The implications of these results can be used in any area of the art, so that the creator is aware of the working steps of the perceived sensations. This study can be applied in the process of creating and can be discussed in the process of work creation. As a result, it can be used as a reference by art creators.ABSTRAKLogika Sensasi dan Fantasi sebagai Langkah dalam Kreasi Seni melalui Practice-Based Research. Tujuan penelitian ini menemukan sebuah tahapan penciptaan karya seni khusnya komposisi dimana sensasi dan fantasi seorang komposer dapat dipahami proses kerjannya secara detail dengan logika sensasi (Deleuze) dan fantasi (Freud). Setiap karya seni yang lahir bukan sekedar sebuah sensasi maupun fantasi seniman yang dituangkan ke dalam karya. Namun proses itu mempunyai logikanya sendiri. Sensasi dan fantasi dalam penciptaan karya seni sangat perlu dan mungkin terus terjadi sampai karya seni itu lahir. Penelitian ini menggunakan pratice-based research dimana pengalaman, karya menjadi dasar sebuah penelitian dengan berbagai macam pendekatan: studi pustaka, analisis isi, filsafat, eksperimental dan beberapa hal yang menguatkan practice-based research. Hasil dari penelitian ini adalah sebuah metode penciptaan seni dengan beberapa tahapan yang perlu dilakukan bahkan sudah dilakukan seorang pencipta; pengalaman estetis, ritme tubuh, chaos, fantasi dan force. Kelima tahapan ini setidaknya menjadi sebuah acuan yang menarik dalam proses karya seni dan bagaimana logika sensasi dan fantasi kita dapat bekerja dengan baik. Implikasi dari hasil ini dapat digunakan wilayah apapun di seni sehingga pencipta sadar akan langkah kerja sensasi yang dirasakan. Penelitian ini bisa diterapkan dalam proses berkarya dan dapat didiskusikan pada tahapan penciptaan dari hasil penelitian ini agar dapat menjadi rujukan oleh para pencipta seni.